(untitled) (Ustozlar uchun, 2024)
ABSTRACT The theme of developing effective listening skills is an essential aspect of personal and professional growth. Effective listening is not merely the act of hearing; it encompasses the ability to comprehend, analyze, and respond to spoken information. An annotation on this theme could explore the following points.